INDEKS GLIKEMIK OYEK DAN TIWUL DARI UMBI GARUT (Marantha arundinaceae L.), SUWEG (Amorphallus campanullatus BI) dan SINGKONG (Manihot utillisima) - Verawati Hasan; Sussi Astuti; Susilawati Susilawati (Jurnal Teknologi & Industri Hasil Pertanian, 2011)
Tubers   are  believed  to have functional   properties because of their fiber (dietary fiber). Utilization of minor tubers like suweg and arrowroot as a raw  material of oyek  and tiwul is not yet widely applied. This study was aimed  to  indentfy   glycemic  index of oyek  and tiwul made from  arrowroot, suweg and cassava. The results showed that  glycemic indexs of arrowroot , suweg and cassava oyek were 41, 42, and 30 respectively. While glycemic index of arroroot, suweg and cassava were 40, 40, and 29.  These results indicates that oyek and tiwul from arrowroot, suweg and cassava  can be classified as food that has low (<55) glycemic index.